The impact of consumer self-confidence and hedonic value on anchored willingness to pay assessments - Douat, Joanna Carolina Guarita (2019)
Prior research on anchoring indicates that arbitrary values can influence human judgment and decision making. This thesis suggests that this behavior is not universal, and it attempts to identify how consumer self-confidence and the hedonic value of goods may shape consumers’ susceptibility to anchoring effect on participants’ willingness to pay. A quantitative approach was adopted in order to demonstrate the association between consumers’ declared willingness to pay (dependent variable), consumer self-confidence (independent variable), hedonic value and anchor as a reference price (manipulated independent variables). Data was collected from experiments performed by 350 international students in New York City. For this study, linear and multiple regressions were considered and two moderation models - simple moderation and a three-way interaction model - were tested, in order to answer the hypotheses. This thesis offers evidence that the hedonic value of products moderates the relationship between anchoring and willingness-to-pay. The results also indicate a three-way interaction between hedonic value, consumer self-confidence, and anchoring effect on willingness-to-pay. Overall, this thesis contributes to the literature of consumer behavior by shedding light on personal traits and product features that can shape anchoring responses. These findings will help researchers and decision makers by suggesting that a product’s monetary valuation is based not only on its perceived value and that it can be affected by variables that were not related. Regarding managerial implications, with the anchoring phenomena and its determinants uncovered, consumers can become conscious of this process to overcome this behavioral bias.